1980
DOI: 10.1007/bf00167369
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of massive stars

Abstract: The evolution of stars with masses between 15M0 and 100M0 is considered. Stars in this mass range lose a considerable fraction of their matter during their evolution.The treatment of convection, semi-convection and the influence of mass loss by stellar winds at different evolutionary phases are analysed as well as the adopted opacities.Evolutionary sequences computed by various groups are examined and compared with observations, and the advanced evolution of a 15Mo and a 25M0 star from zero-age main sequence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 115 publications
0
10
0
Order By: Relevance
“…Data gathered at various wavelengths (mainly in the UV and radio ranges) have shown that massive O and B stars (M > 20 Mo) shed a considerable amount of mass in the form of stellar winds (e.g., de Loore, 1980). The mass-loss from O stars is on the order of 10 -7 M o yr-l, Of stars reaching 10 -6 M o yr-1.…”
Section: A Massive Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data gathered at various wavelengths (mainly in the UV and radio ranges) have shown that massive O and B stars (M > 20 Mo) shed a considerable amount of mass in the form of stellar winds (e.g., de Loore, 1980). The mass-loss from O stars is on the order of 10 -7 M o yr-l, Of stars reaching 10 -6 M o yr-1.…”
Section: A Massive Starsmentioning
confidence: 99%
“…They are thought to be a late, but comparatively brief (a few 105 yr, e.g., Maeder and Lequeux, 1982) evolutionary stage of O stars, perhaps immediately preceded by an Of phase (Conti et al, 1979). Several models exist for this transition (Maeder, 1982;de Loore, 1980), but it is thought that all O stars above ~ 23 M o display the 'WR phenomenon' before becoming supernovae (Maeder and Lequeux, 1982). However, the WR stars appear to be linked somewhat less frequently than O stars with OB associations (or giant H II regions as their tracers), since at least ~ 60~o are isolated objects (Vand der Hucht et al, 1981).…”
Section: A Massive Starsmentioning
confidence: 99%
“…Therefore the amount and mode of mass loss in early (blue) phases will significantly affect all subsequent evolution, whereas the amount and mode of mass loss as intermediate to late ty_ pe stars, may control the reappearance of the models as blue evolved objects. The recent reviews by de Loore (1979Loore ( , 1980 on the evolution of massive stars undergoing mass loss by stellar wind during core and shell H-burning phases make superflous here a deta_i_ led description of those results. Therefore we will be onlyconcerned with the most recent advancements, yet the main re suits on the subject will be also outlined.…”
Section: Evolution Of Massive Stars With Mass Lossmentioning
confidence: 98%
“…As is well known, the mass exchange, and more recently a combination of mass exchange and mass loss by stellar wind, offers an easy and straightforward scenario for the production of WR stars in binary systems. The situation has been recently reviewed by de Loore (1979Loore ( , 1980. On the contrary, the possibility that mass loss by stellar wind may transform a single 0 type star into a WR star, as suggested some time ago by Conti (1976a), is still an unsettled question.…”
Section: Evolutionary Scenario For Wr Starsmentioning
confidence: 99%
“…The conventional theories for the evolution of close binaries usually assume that the synchronism of the rotation with the orbital motion is always reached (Kippenhahn & Weigert 1967;De Loore 1980;Huang & Taam 1990;Vanbeveren 1991;De Greve 1993). The potential for a synchronous rotating component in a Roche model is given by…”
Section: Equipotential and The Equivalent Spherementioning
confidence: 99%